An investigation into water consumption by university students: actions, beliefs and perceptions - Leonardo André Broering; Julia Michel; Elisa Henning; Andreza Kalbusch; Andrea Cristina Konrath (Discover Water)
Abstract Sustainable development requires water resources, and the supply of water is directly linked to economic growth, political and social issues. This article presents the findings of a research study conducted to identify actions, beliefs and perceptions regarding water consumption among students and the possible associations between actions related to water conservation and demographic, socioeconomic and cultural variables. In addition, we aimed at finding any changes in water use habits due to the COVID-19 pandemic. The study was carried out at a university in the city of Joinville (southern Brazil). Non-probabilistic quota sampling was implemented and a total of 246 responses were obtained. Exploratory data analysis was performed by means of descriptive and graphical measures. Classical statistical tests were applied to identify possible associations. The results provided information on the use of water for personal hygiene and cleaning, among others. Based on the understanding of the consumption habits, more targeted awareness-raising actions can be prioritized.